2017
DOI: 10.1042/bsr20170755
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-211/BDNF axis regulates LPS-induced proliferation of normal human astrocyte through PI3K/AKT pathway

Abstract: Spinal cord injury (SCI) makes a major contribution to disability and deaths worldwide. Reactive astrogliosis, a typical feature after SCI, which undergoes varying molecular and morphological changes, is ubiquitous but poorly understood. Reactive astrogliosis contributes to glial scar formation that impedes axonal regeneration. Brain-derived neurotrophic factor (BDNF), a well-established neurotrophic factor, exerts neuroprotective and growth-promoting effects on a variety of neuronal populations after injury. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(26 citation statements)
references
References 48 publications
0
26
0
Order By: Relevance
“…Recent study have stated that miR-211 could modulate inflammatory diseases through regulating PI3K/AKT pathway [28]. Further, LSZ has been proven to be an important regulator of the PI3K/AKT pathway [29,30].…”
Section: Discussionmentioning
confidence: 99%
“…Recent study have stated that miR-211 could modulate inflammatory diseases through regulating PI3K/AKT pathway [28]. Further, LSZ has been proven to be an important regulator of the PI3K/AKT pathway [29,30].…”
Section: Discussionmentioning
confidence: 99%
“…NHAs. qPCR results showed that LPS significantly inhibited the expression of miRNAs [2,[11][12][13] associated with proliferation and apoptosis of NHAs (p < 0:05, p < 0:01), and the addition of ISO reversed these inhibitory effects to a certain extent. In particular, among all examined miRNAs, miR-206 was the most significantly reversed one (Figure 2, p < 0:01).…”
Section: Iso Upregulated Mir-206 Expression Inmentioning
confidence: 97%
“…It has been reported that the normal human astrocytes (NHAs) can minimize primary damage and repair damaged tissues. However, under certain pathological conditions, NHAs can change to become reactive NHAs [2], and reactive NHAs are one of the main sources of proinflammatory cytokines in the brain [3]. NHAs are involved in the development of a variety of neurodegenerative diseases [4]; therefore, studying the mechanism of reactive NHAs is helpful for the development of protective strategies for neurodegenerative diseases induced by central nervous system inflammation.…”
Section: Introductionmentioning
confidence: 99%
“…Some microRNAs also affect the polarization of microglia to regulating inflammation. For example, miR-125b promotes toxic M1 polarization, and miR-124 contributes to protective M2 polarization of microglia (Parisi et al, 2016;Yu et al, 2017) -140, miR-211, miR-145, miR-146a, miR-147b, miR-132, and miR-181, not only inhibit the production of pro-inflammation factors but also act against reactive astrocyte proliferation through the PI3K/AKT pathway (Hutchison et al, 2013;Iyer et al, 2012;Tu et al, 2017;Van Scheppingen et al, 2018;Wang, Yang, & Tzeng, 2015;Zhang, Wu, Li, & Zhou, 2017; expression (Dentesano et al, 2014). The suppression of neuroinflammation can also be mediated by modulating the signaling of additional pairs of interacting molecules, such as CD22-CD45, CD172A-CD47, and ICAM5-leukocyte β2-integrins (Gahmberg, Tian, Ning, & Nyman-Huttunen, 2008;Mott et al, 2004;Numakawa et al, 2004).…”
Section: The Balance Of Pro-/anti-inflammation Regulationsmentioning
confidence: 99%